Pengaruh Customer Relationship Management (CRM) Dan Inovasi Produk Terhadap Loyalitas Pelanggan - Fahmi Abdul Azis; Suci Putri Lestari; Kusuma Agdhi Rahwana (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2023)
This study aims to determine the effect of CRM and product innovation on customer loyalty SMeS Bordir. The method used in this study is a quantitative method with a descriptive approach, with a research sample of 100 respondents and the analytical tool used in this study is multiple linear regression. The results of this study indicate that CRM and Product Innovation have a significant simultaneous effect on Customer Loyalty in SMeS Bordir. CRM and Product Innovation have a significant partial effect on Customer Loyalty to SMeS Bordir.